PENGARUH PROFITABILITAS, KOMITE AUDIT, PERGANTIAN AUDITOR, DAN UKURAN PERUSAHAAN TERHADAP INTEGRITAS LAPORAN KEUANGAN - Nabila, Nabila; Zakaria, Adam; Purwohedi, Unggul (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2023)
This study was conducted with the aim of determining the effect of profitability, audit committee, auditor switching, and firm size on integrity of financial statements. The research use documentation method by gathering data from the website https://idx.co.id/ and also utilized literature review to find relevant theories. The research approach used was quantitative, utilizing secondary data. Data collection was performed using purposive sampling, where 32 companies were selected from the entire food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2020-2022, resulting in a total sample of 96. The data collected were then analyzed using multiple linear regression with SPSS 29 software. The results of the study indicated that profitability and firm size have an effect on the integrity of financial statements, while the audit committee and auditor switching do not have an effect on the integrity of financial statement. Based on these findings, recommendations for further research include adding additional observation years, expanding and increasing the sample size, and considering the inclusion of other variables that may potentially affect the integrity of financial statement